Regulatory Roles of Related Long Non-coding RNAs in the Process of Atherosclerosis - Meng, Qingyu; Pu, Luya; Luo, Xizi; Wang, Baisen; Li, Fan; Liu, Bin (Frontiers in Physiology, 2020)
Atherosclerosis (AS) is the main cause of coronary heart disease, cerebral infarction and peripheral vascular disease, which comprise serious hazards to human health. AS is characterized by the deposition of lipids on the interior walls of blood vessels, causing an inflammatory response of immune cells, endothelial cells and smooth muscle cells, and a proliferation cascade reaction. Despite years of research, the underlying pathogenesis of AS has not been fully defined. Recent advances in our understanding of the molecular mechanisms by which noncoding RNA influences the initiation and progression of AS have shown that long noncoding RNAs (lncRNAs) regulate important stages in the atherosclerotic process. In this review, we summarize current knowledge of lncRNAs that influence the development of atherosclerosis. We review regulatory processes of lncRNAs on core stages of atherosclerotic progression, including lipid metabolism, inflammation, vascular cell proliferation, apoptosis, adhesion and migration, and angiogenesis. A growing body of evidence suggests that lncRNAs have great potential as new therapeutic targets for the treatment of vascular diseases.